Photodynamic Antimicrobial Chemotherapy Reduces Bacterial Load in Live Feeds in Aquaculture - K Moideen, Sulfiya; Abdulaziz, Anas (SAARC Journal of Agriculture, 2023)
Live feeds are one of the route of entry of pathogenic bacteria in larval rearing systems in aquaculture. Current study discusses the disinfection of bacteria associated with live feed (Artemia nauplii) using photodynamic antimicrobial chemotherapy (PACT). More than 90 % of Aeromonas hydrophila in solution and total bacteria associated with live feed were killed on exposure to 5 μM of curcumin under photoexcitation for 30 minutes. The cell wall of A. hydrophila was disrupted by the reactive oxygen species generated by photoexcited curcumin. Up to 50 μM curcumin and their photoexcitation products were not toxic to Artemia nauplii. The findings of the current study propose photodynamic antimicrobial chemotherapy as a propitious tool for One Health approach and restricting the use of antibiotics in aquaculture settings. SAARC J. Agric., 21(2): 239-250 (2023)